Adición del cushuro (Nostoc sphaericum) liofilizado como estabilizante en yogurt natural batido - Ramirez Alvarez, Yuri Athena (2025)
In recent years, diets based on algae such as cushuro have gained greater acceptance due to their well-recognized health benefits. The objective of this study was to determine the effectiveness of freeze-dried cushuro as a stabilizer when added to stirred natural yogurt, using fresh milk obtained through mechanical milking. Before processing, the milk was subjected to physicochemical analyses, with pH (6.57), acidity (0.16%), and density (1.031 g/ml); subsequently, yogurt treatments were prepared with cushuro concentrations of 0.05%, 0.10%, and 0.15%, and their physicochemical properties (pH, acidity, syneresis, viscosity, density) and organoleptic characteristics (odor, color, taste, texture, appearance) were analyzed. The results indicated that the treatment with 0.15% cushuro showed the highest viscosity (2.114 Pa·s) and the lowest syneresis (5.126%), demonstrating a significant improvement in yogurt stability due to greater water retention in the protein matrix. On the other hand, the sensory analysis conducted by 38 semi-trained panelists aged 15 to 65 years showed that yogurt with 0.05% cushuro was the most accepted in terms of aroma, taste, and texture, achieving an average score of 3.89 out of 5. Statistical analysis using ANOVA and post hoc tests (Dunnett and Tukey) confirmed that there were significant differences (p < 0.05) among the treatments. Finally, the nutritional analysis of the best yogurt treatment revealed a moisture content of 83.14%, protein 10.74%, fat 3.93%, and ash 5.14%, indicating an adequate nutritional contribution, especially in terms of protein. These results support the use of freeze-dried cushuro as an effective functional ingredient and stabilizer in yogurt.